The effects of combination behavioural intervention of nutritional education and exercise (combine) on oxidate stress markers in obese subject - Rahimah, Zakaria (Pusat Pengajian Sains Perubatan, 2012)
Alterations in the levels of oxidative stress and haemostatic markers have been proposed as one of the mechanisms for obesity-related cardiovascular disease. This study aims to evaluate the effect of 12-week behavioral lifestyle modification program on the oxidative stress levels in obese subjects. This is an interventional prospective study conducted from April 2009 through December 2010. Thirty four obese adult recruited from the Obesity Clinic, Hospital Universiti Sains Malaysia participated in the 12-week behavioral lifestyle modification program consisting of diet and exercise interventions. Body weight, BMI and body fat were significantly reduced after 12-week interventions. Plasma GPx activity and 4-HNE concentration increased significantly after 12-week interventions. Other enzymatic antioxidant activities such as CAT and SOD increased, and GSH:GSSG ratio reduced but the changes were not statistically significant. Plasma fibrinogen, factor VII, TAFI, t-PA and PAI-1 levels were significantly decreased and plasma Heparin Cofactor II level was significantly increased after 12-week intervention. In conclusion, diet and exercise interventions reduce cardiovascular risk factors by reducing body fat, increasing enzymatic antioxidant defense and beneficially altering the levels of haemostatic markers in obese adults.